МАДАНИЯТЛАРАРО МУЛОҚОТНИ ЎҚИТИШДА ЧЕТ ТИЛИНИНГ АҲАМИЯТИ - Азимова Мохигул Тожиддиновна; Турсуналиева Шохсанам Кахрамон кизи; Сапарбаева Мадина (Journal of new century innovations, 2023)
The article deals with the widely recognized international standards of the European Council “Teaching foreign language of common European competences:learning,teaching and evaluation of foreign language” to get CEFR competencies in the era of globalization.